Cara Berpakaian Orang Kristen dalam Gereja - Putri Pramesti Polii; Boy Lumoindong; Juwinner Dedy Kasingku (Journal on Education, 2023)
The way a person dresses reflects their own self-image. At this time, there are numerous Christians who do not understand the concept of Christian clothing that should be worn when going to church. Therefore, this research was conducted so that we could see what kind of clothing is appropriate in the church. This research uses qualitative research methods along with descriptive methods and library research. We discovered that clothing that is polite, clean, polite, and simple can reflect God's image in every Christian because God looks at our hearts, not the glamor or style of the clothes we wear, by examining various sources of information and perceptions. This is very important to research so that many people understand it better and don't blame it too much.